Environmental Factor-Mediated Transgenerational Inheritance of Igf2r Hypomethylation and Pulmonary Allergic Response via Targeting Dendritic Cells - Suen, Jau-Ling; Wu, Tai-Ting; Li, Yue-Hyuan; Lee, Chin-Lai; Kuo, Fu-Chen; Yan, Pearlly S.; Wu, Chia-Fang; Tran, Mita; Wang, Chien-Jen; Hung, Chih-Hsing; Wu, Ming-Tsang; Chan, Michael W. Y.; et al. (Frontiers in Immunology, 2020)
The developmental origin of allergic diseases has been suggested, but the molecular basis remains enigmatic. Exposure to environmental factors, such as di-(2-ethylhexyl) phthalate (DEHP; a common plasticizer), is suggested to be associated with increased childhood allergic asthma, but the causal relationship and its underlying mechanism remain unknown. This study explored the transgenerational mechanism of DEHP on allergic asthma and dendritic cell (DC) homeostasis through epigenetic modification. In a murine model, ancestral exposure of C57BL/6 mice to low-dose DEHP led to trans-generational promoter hypomethylation of the insulin-like growth factor 2 receptor (Igf2r), concomitant with enhanced Igf2r expression and increased apoptosis prominently in CD8α+ DCs upon ligand stimulation, with consequent reduction in their IL-12 secretion and subsequent T cell-derived IFN-gamma, thereby promoting a default Th2-associated pulmonary allergic response. Increased apoptosis was also noted in circulating IGF2Rhigh human DCs. Further, in human placenta, the methylation level at the orthologous IGF2R promoter region was shown to be inversely correlated with the level of maternal DEHP intake. These results support the importance of ancestral phthalate exposure in conferring the trans-generational risk of allergic phenotypes, featuring hypo-methylation of the IGF2R gene and dysregulated DC homeostasis.